Chemical composition of manganese nodules from the Australian region - L C Noakes; H A Jones (PANGAEA, 2022)
Fifteen manganese nodules from the Australian region have been analysed by the Bureau of Mineral Resources (BMR) from the Department of Minerals and Energy, Australia. These samples were analysed for Fe, Mn Ni, Cu and Co using Atomic Absorption Spectrophometry.